Comparison of Flow and Compression Properties of Four Lactose-Based Co-Processed Excipients: Cellactose® 80, CombiLac®, MicroceLac® 100, and StarLac® - Dominik, Martin; Vraníková, Barbora; Svačinová, Petra; Elbl, Jan; Pavloková, Sylvie; Prudilová, Barbora Blahová; Šklubalová, Zdeňka; Franc, Aleš (Pharmaceutics, 2021)
The utilization of co-processed excipients (CPEs) represents a novel approach to the preparation of orally disintegrating tablets by direct compression. Flow, consolidation, and compression properties of four lactose-based CPEs-Cellactose® 80, CombiLac®, MicroceLac® 100, and StarLac®-were investigated using different methods, including granulometry, powder rheometry, and tablet compaction under three pressures. Due to the similar composition and the same preparation technique (spray drying), the properties of CPEs and their compacts were generally comparable. The most pronounced differences were observed in flowability, undissolved fraction after 3 min and 24 h, energy of plastic deformation (E2), ejection force, consolidation behavior, and compact friability. Cellactose® 80 exhibited the most pronounced consolidation behavior, the lowest values of ejection force, and high friability of compacts. CombiLac® showed excellent flow properties but insufficient friability, except for compacts prepared at the highest compression pressure (182 MPa). MicroceLac® 100 displayed the poorest flow properties, lower ejection forces, and the best mechanical resistance of compacts. StarLac® showed excellent flow properties, the lowest amounts of undissolved fraction, the highest ejection force values, and the worst compact mechanical resistance. The obtained results revealed that higher compression pressures need to be used or further excipients have to be added to all tested materials in order to improve the friability and tensile strength of formed tablets, except for MicroceLac® 100.
Keywords: StarLac®; spray drying; Cellactose® 80; CombiLac®; co-processed excipients; MicroceLac® 100